Mickey Mouse monopoly disney, childhood & corporate power - Sun, Chyng-Feng; Picker, Miguel; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 2001)
Mickey Mouse Monopoly takes a close and critical look at the animated films produced by the Disney Company, and at the world these films create (in terms of the stories told about race, gender and class) and reaches disturbing conclusions about the values propagated under the guise of innocence and fun
Title from title screen
Photography, editing and music by Miguel Picker
Narrator: Monique Fordham
Keywords: Disney characters -- Political aspects; Children's films -- Political aspects